Explaining and Drawing up Priorities of Dimensions and Factors of Place Attachment in University Campuses from Students’ Point of View; The Cases of the Faculty of Architecture, Islamic Azad University, Najaf Abad, Khorasgan, and Khomeini Shahr - Elahe Nadi; Mansoureh Kian Erthi (صفه)
First-year students in transition from hometown to university are generally confronted by intellectual and social challenges as well as those associated with the formation of new place attachments. Place attachment is an emotional and positive connection between a person and a place that makes space a special place for people, and essential for attracting students to a new educational environment. So, it is important to know the variables of place attachment in the design of campuses. With the developments in the field of science and attention to outdoor education, the design of campuses to improve the quality of education are of particular importance. The purpose of this study was to explain and prioritise the dimensions and factors of place attachment in university campuses near major cities and the faculties of architecture of Najafabad, Khorasgan and Khomeini Shahr Azad University (all within easy reach of Isfahan). It is an applied research, using descriptive-analytical and qualitative and quantitative (combined).At the beginning, researches in the fields of environmental psychology, place attachment and university campuses were reviewed and the dimensions and factors of place attachment were extracted. Then, the three samples were examined and by completing the observation checklist and the questionnaire form obtained from the theoretical studies, the dimensions and factors of place attachment were evaluated from the students’ point of view. The results show that the ten dimensions of place attachment from the perspective of students in university campuses have been of varying importance. Familiarity with place, roots, meaning of place, social connection with the place, satisfaction with the place, place attachment, Emotional connection with the place, dependence on the place, connection with nature and place identity, being priorities respectively, and physical factors, social and semantic factors of the place, being the first three, and the place activity factor, being less important. To conclude, design solutions are proposed in accordance with the presented prioritization.